The effects of self-efficacy, social support, and mental toughness on tennis umpires` professional identity: a study based on a latent variable mediation model - Zhou, X.; Luo, L.; Liu, Q.; Li, B.; Wen, L. (Frontiers in Psychology, 2025)
Purpose: To explore the relationship between self-efficacy and professional identity among tennis umpires, and to explore the mediating role of mental toughness and social support in this process.